Ertapenem-Induced Encephalopathy in a Patient With Normal Renal Function - S. Scott Sutton PharmD; Mark Jumper PharmD; Sean Cook DO; Babatunde Edun MD; Michael D. Wyatt PhD (SAGE Publishing, 2017)
Drug-induced neurotoxicity is a rare adverse reaction associated with ertapenem. Encephalopathy is a type of neurotoxicity that is defined as a diffuse disease of the brain that alters brain function or structure. We report a patient with normal renal function who developed ertapenem-induced encephalopathy manifesting as altered mental status, hallucinations, and dystonic symptoms. The patient's symptoms improved dramatically following ertapenem discontinuation, consistent with case reports describing ertapenem neurotoxicity in renal dysfunction. Since clinical evidence strongly suggested ertapenem causality, we utilized the Naranjo Scale to estimate the probability of an adverse drug reaction to ertapenem. Our patient received a Naranjo Scale score of 7, suggesting a probable adverse drug reaction, with a reasonable temporal sequence to support our conclusion.